Sensitivity and Specificity in Urine Bladder Cancer Markers - Is it that Simple? Comment - Roghmann, Florian; Goebell, Peter; Dyrskjot, Lars; van Rhijn, Bas W. G.; Kaefferlein, Heiko U.; Hakenberg, Oliver; Stenzl, Arnulf; Burger, Maximilian; Pesch, Beate; Benderska-Soeder, Natalya; Schmitz-Draeger, Bernd J. (Bladder Cancer, 2022)
Marker research, and in particular urine bladder cancer marker research throughout the past three decades, devours enormous scientific resources in terms of manpower (not to mention time spent on reviewing and editorial efforts) and financial resources, finally generating large numbers of manuscripts without affecting clinical decision making. This is mirrored by the fact that current guidelines do not recommend marker use due to missing level 1 evidence.
CRIS-Team WoS Importer:2022-04-01
Keywords: Urinary tumor markers; bladder cancer; diagnosis; sensitivity; specificity